2002
DOI: 10.1002/ijc.10647
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative, antiangiogenic and proapoptotic activity of h‐R3: A humanized anti‐EGFR antibody

Abstract: The epidermal growth factor receptor (EGFR) proto-oncogene is frequently overexpressed in tumors of epithelial origin. This event is thought to be causative for tumor development and progression and henceforth associated with poor prognosis. The recent considerable interest in developing EGFR-targeting agents resulted in derivation of the monoclonal, humanized, neutralizing antibody h-R3, which binds to the extracellular domain of EGFR with high affinity and strongly inhibits EGFR-dependent cellular transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
119
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 30 publications
5
119
1
Order By: Relevance
“…Further, a close relationship between EGFR/VEGF has been postulated to promote angiogenesis (Rak et al, 2000). Whereas earlier studies indicated that VEGF is induced in tumours after irradiation (Gorski et al, 1999), nimotuzumab has shown to downregulate VEGF expression at the RNA and protein level after treatment in A431 tumour xenografts in vivo (Crombet-Ramos et al, 2002). In agreement with that, we found a 60% of reduction in the total area of the vessels in tumour specimens from mice treated with nimotuzumab.…”
Section: Discussionsupporting
confidence: 89%
“…Further, a close relationship between EGFR/VEGF has been postulated to promote angiogenesis (Rak et al, 2000). Whereas earlier studies indicated that VEGF is induced in tumours after irradiation (Gorski et al, 1999), nimotuzumab has shown to downregulate VEGF expression at the RNA and protein level after treatment in A431 tumour xenografts in vivo (Crombet-Ramos et al, 2002). In agreement with that, we found a 60% of reduction in the total area of the vessels in tumour specimens from mice treated with nimotuzumab.…”
Section: Discussionsupporting
confidence: 89%
“…Together these results suggest that the efficacy of nimotuzumab monotherapy is a prerequisite for augmentation of radioresponse by this mAb. Nimotuzumab was previously shown to induce the regression of A431 tumour xenografts in vivo as a result of inhibition of both tumour cell proliferation and tumour angiogenesis (Crombet-Ramos et al, 2002). Immunohistochemical analysis of tumour specimens from head and neck cancer patients treated with the combination of nimotuzumab and radiation also showed evidence of antiproliferative and antiangiogenic effects (Crombet et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In a preclinical study, nimotuzumab showed marked antiproliferative, proapoptotic, and antiangiogenic effects in tumours that overexpress EGFR (Crombet-Ramos et al, 2002). In early clinical trials, nimotuzumab has shown a longer half-life and a greater area under the curve (AUC) in comparison with other anti-EGFR antibodies (Crombet et al, 2003).…”
mentioning
confidence: 99%
“…The in vitro antiproliferative activity of nimotuzumab was tested in both two and three dimensional A431 squamous cell carcinoma cultures. 7 There was a dose dependent inhibition of vascular endothelial growth factor (VEGF) expression in A431 monolayer cultures. In studies with A431 subcutaneous tumor xenografts, northern blot analysis of the tumors confirmed VEGF inhibition by nimotuzumab.…”
Section: Functional Attributes Of Nimotuzumabmentioning
confidence: 99%